Fenced off: Measuring growing restrictions on resource access for smallholders in the Argentine Chaco. (September 2021) - del Giorgio, Olivia; Messager, Mathis Loïc; le Polain de Waroux, Yann
Abstract: The rapid expansion of commodity agriculture worldwide is threatening forest ecosystems and the livelihoods of millions of people who depend on them. Forest-dwelling smallholders in agricultural frontier regions are facing mounting pressures due to changes in land control, notably through the privatization and enclosure of natural resources. Impacts of agricultural expansion on smallholders are often approximated by measuring deforestation, yet changes in land control and associated pressures on smallholder livelihoods occur well beyond the limits of deforested areas. We propose a novel approach to evaluate changes in access to land for smallholders stemming from gradual changes in land control along commodity frontiers. We apply this approach in the Argentine Gran Chaco, a region that has experienced amongst the highest global rates of deforestation for agriculture in recent years. Our findings suggest that access to natural resources for smallholders has been reduced far beyond what would be expected if only looking at deforestation, and that the degree to which access has decreased differs between livelihood activities. As such, this study highlights the fact that forest smallholders are likely facing pressures to move or shift their livelihood strategies well in advance of the actual conversion of forest in their immediate vicinity. Highlights: Expansion of commodity frontiers limits smallholder access to natural resources. Deforestation alone does not reflect livelihood impacts of commodity frontiers. We propose a novel spatial index capturing access changes for different livelihoods. Index reveals pervasive and differential pressures on livelihoods in the Gran Chaco.